ANALISIS PERSEPSI KUALITAS PERKULIAHAN DI LABORATORIUM PERKANTORAN DAN SEKRETARI PROGRAM PENDIDIKAN VOKASI UNIVERSITAS INDONESIA - Istiadi Istiadi; Mohammad Ridha (Program Pendidikan Vokasi Universitas Indonesia, 2016)
Laboratory of the study Program is the on factor that imfluence the quality of student in the process of theirstudy in Vocational Program . In order that, laboratory must become the crucial factor in producing qualifiedalumni.The quality of teaching ini laboratory in general was imfluenced some factors like: lecturer/instructur,curicullum, tools or su pported facilities in laboratory. For that reason, in this research we want to know thegeneral of student in laboratory teaching. Factors that was identified included : degree of studentsatisfaction, quality of teaching, and laboratory supporting facilities . Output of this research is benefited asthe input in developing the ideal office and Secretary Laboratory that sincronized with student needs.Keyword; Laboratory, quality of teaching, facility, curicullum, student satisfaction.